A generic approach for the design of organizational decision support systems (ODSS) - Chalal, Rachid; Nader, Fahima (INFOCOMP Journal of Computer Science, 2007)
The paper proposes a generic approach to design and develop an Organizational Decision Support System (ODSS). This approach is based at the follows definition: the ODSS is considered as the experts' memory and their decision-taking. Therefore, the ODSS is constituted by two elements, a strategic DSS and a specific referential of the decision situation. Our generic approach for ODSS design is based on the MUSIC (Management and Use of Co-operative Information Systems) model. An illustration of the approach is presented. The type of ODSS presented (risk estimation and management of innovative projects made during the bidding phase) is generic among process-oriented organizations.